OSIALISASI BAHAYA HIPERTENSI DI DUSUN WONOLOBO - Aidha Trisanty (Asian Journal of Innovation and Entrepreneurship, 2015)
Hypertension is an increase in blood pressure in arteries. Hypertension is a disorder of circulatory system that causes a rise in blood pressure above normal values.Hypertension is a global health problem that needs attention because it can lead todeath in the developed and developing countries. The prevalence of hypertension inIndonesia always increases. As time goes by, hypertension is not only caused by theheredity. Implementing the unhealthy lifestyle is the biggest factor that causedhypertension.  Dusun Wonolobo that located in Pandean, District Ngablak, Magelang has quite alot of people who have hypertension. The habit of the society that consumes tea and coffee can be one of the causes of hypertension. Socializing hypertension can help dusun society to know the factors that cause hypertension and the ways to decrease the bloodpressures. Knowing the causes factor, prevention and symptoms of the increasing bloodpressure can help the society in decreasing the number of hypertension.